Optimizing the Analytical Performance of Substrate-Integrated Hollow Waveguides: Experiment and Simulation. Issue 12 (December 2019) - Hagemann, L. Tamina; Ehrle, Sonja; Mizaikoff, Boris
The goal of this technical note was to compare experimentally and via simulation of eight substrate-integrated hollow waveguide (iHWG) designs, and to predict promising future iHWG structures in lieu of experiments. The iHWGs differed in their geometry (i.e., inlet funnel cross-section and inner channel cross-section), as well as in their material properties (i.e., type of metal, polish of inner channel). Experimentally, calibration functions of isobutane as a model analyte were determined, and the analytical figures of merit, i.e., signal-to-noise ratio, limit of detection, were evaluated for each iHWG. Evaluation of the amount of radiation incident at the real-world and simulated detector revealed that experiment and simulation were in excellent agreement. While material and quality of the inner channel wall did not have a significant influence on the performance, the iHWG geometry profoundly affected the performance in terms of light throughput: Increasing the inlet funnel dimensions and the inner channel cross-section benefits light throughout, and thus, the analytical signal. Based on these results, simulations of not yet fabricated iHWGs were performed and promising new iHWG structures were suggested.